2012
DOI: 10.1044/1059-0889(2012/12-0014)
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-Based Systematic Review of Directional Microphones and Digital Noise Reduction Hearing Aids in School-Age Children With Hearing Loss

Abstract: Purpose The purpose of this evidence-based systematic review was to evaluate the efficacy of digital noise reduction and directional microphones for outcome measures of audibility, speech recognition, speech and language, and self- or parent-report in pediatric hearing aid users. Method The authors searched 26 databases for experimental studies published after 1980 addressing one or more clinical questions and meeting all inclusion criteria. The authors evaluated studies for methodological quality and report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 58 publications
2
26
0
4
Order By: Relevance
“…These multiple microphone beamformers have been incorporated successfully into hearing aids since the 1990s and two systematic reviews identified weak to moderate evidence of their effectiveness in improving speech perception in noise (Bentler, 2005;McCreery et al, 2012;Ricketts and Dhar, 1999;Ricketts and Henry, 2002). However, the first adaptive beamforming algorithms integrated into CI speech processors were not commercially introduced until 2005 (Spriet et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…These multiple microphone beamformers have been incorporated successfully into hearing aids since the 1990s and two systematic reviews identified weak to moderate evidence of their effectiveness in improving speech perception in noise (Bentler, 2005;McCreery et al, 2012;Ricketts and Dhar, 1999;Ricketts and Henry, 2002). However, the first adaptive beamforming algorithms integrated into CI speech processors were not commercially introduced until 2005 (Spriet et al, 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Modern devices employ sophisticated digital signal processing that often incorporates noise suppression, dynamic gain control, and directional microphones (e.g., [23,24]). The directional microphones amplify sound in front of the listener while limiting it from the sides and behind [19]; however, they generally do not improve the localization of sound without visual stimuli (speaker's face in view) [23]. For bilateral hearing aid users (both ears), each device works independently, which has destructive effects on the binaural cues necessary to locate sound [1].…”
Section: Hearing Aids and Cochlear Implantsmentioning
confidence: 98%
“…Children with severe to profound UHL are less likely to receive benefit from hearing aids (Kiese-Himmel, 2002;Updike, 1994). Another factor is background noise: hearing aids are less beneficial in noise than in quiet, although directional microphones may improve performance in noise (Ching et al, 2009;McCreery, Venediktov, Coleman, & Leech, 2012). Age at hearing aid fitting is another important factor, as hearing aids seem to be more beneficial if they are fit before the age of 5 to 6 years.…”
Section: Hearing Aidsmentioning
confidence: 98%